Characterization of argon ion irradiation induced changes in microstructure and mechanical property of binary Zr−2.9 wt% Sn alloy. (January 2022) - Devi, Aruna; Neogy, S.; Sharma, S.K.; Menon, R.; Tewari, R.
Abstract: In this study, we report the investigation of microstructural and mechanical property changes in binary Zr−2.9 wt% Sn alloy induced by room temperature heavy ion (Ar 9+ ) irradiation to fluences ranging from 3.1 × 10 15 to 4.17 × 10 16 Ar 9+ cm -2 . S-parameter, probed using positron annihilation spectroscopy, showed an increase with fluence. Changes in microstructural attributes, viz., the coherently scattering domain size, microstrain, dislocation density and, residual stress, were ascertained through grazing incidence X-ray diffraction. A decrease in domain size and increase in both microstrain and dislocation density were observed in addition to the development of compressive stress in place of tensile after irradiation. The hardness of the irradiated samples, probed by nanoindentation, was found to be higher in comparison to unirradiated one. Transmission electron microscopy investigation exemplified the formation of - and - type dislocation loops upon irradiation. The above findings could be rationalized on the basis of the defects generated during Ar 9+ heavy ion irradiation. Highlights: Ar 9+ ion irradiation of binary Zr− 2.9 wt% Sn alloy. Distribution of defects observed experimentally. Domain size, microstrain and dislocation density characterization using GI-XRD. Change in nature of residual stress from tensile to compressive upon irradiation. Characterization of dislocation loops and probing of irradiation hardening.